HUBUNGAN KADAR HEMOGLOBIN TERHADAP KETAHANAN AEROBIK DAN KEKUATAN OTOT PADA LANJUT USIA - Sandy Theresia; Nelly Tina Widjaja; Maria Dara Novi Handayani (Atma Jaya Catholic University of Indonesia, 2019)
Introduction: The increase in the elderly population causes many health problems. One of them is the decline in physical function, making the elderly have difficulty performing daily activities. Some studies suggest the relation between decreased hemoglobin level with aerobic endurance and muscle strength. This study aims to determine the relation between hemoglobin and aerobic endurance, muscle strength in the elderly. Methods: This research is an analytic-correlative research conducted cross-sectionally on 84 respondents in Kelurahan Cideng, Central Jakarta. The data is collected from questionnaires, hemoglobin level (sodium lauryl sulfate-hemoglobin method), and physical performance tests (2-minutes test, arm curl test, and chair stand test). Results: The mean hemoglobin level is 14.37 g/dL. There was a significant relation between hemoglobin with aerobic endurance (p<0.05), whereas no significant relation between hemoglobin with upper and lower limb muscle strength (p>0.05). Conclusion: There was a relation between hemoglobin level with aerobic endurance in the elderly.